9th ANNUAL CONFERENCE NANO & MACRO MECHANICS 2018 - Editorial, Foreword (Acta Polytechnica CTU Proceedings)
The 9th annual conference Nano & Macro Mechanics was held in Prague, in September 20, 2018. Scientific comittee: Tomáš Plachý Pavel Tesárek Pavel Padevět Petr Bittner Aleš Jíra Daniel Rypl Jan Vorel Bořek Patzák Lenka Melzerová Local organizing comittee: Petr Bittner Tomáš Plachý Pavel Padevět Pavel Tesárek Tereza Plaček Otcovská Barbora Mužíková Zdeněk Prošek Guarantor of the peer review proces: Pavel Padevět Guarantor of language editing: Tomáš Plachý